2018
DOI: 10.1002/aenm.201803151
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Soluble Cu Complex as Molecular Catalyst for Electrocatalytic CO2 Reduction on Graphene‐Based Electrodes

Abstract: We report that a structurally simple molecular 1,10-phenanthroline-Cu complex on a mesostructured graphene matrix can be active and selective toward CO2 reduction over H2 evolution in an aqueous solution. The active sites consisted of Cu(I) center in a 2 distorted trigonal bipyramidal geometry, which enabled the adsorption of CO2 with η 1 -COO-like configuration to commence the catalysis, with a turnover frequency of ~45 s -1 at -1 V vs reversible hydrogen electrode. Using in-situ infrared spectroelectrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 70 publications
1
83
0
2
Order By: Relevance
“…[103] The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which allows the adsorption of CO 2 with η1-COO-like configuration to commence the catalysis, with a turnover frequency of ≈45 s −1 at −1 V versus RHE. [103] The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which allows the adsorption of CO 2 with η1-COO-like configuration to commence the catalysis, with a turnover frequency of ≈45 s −1 at −1 V versus RHE.…”
Section: Other Metal-based Catalystsmentioning
confidence: 99%
“…[103] The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which allows the adsorption of CO 2 with η1-COO-like configuration to commence the catalysis, with a turnover frequency of ≈45 s −1 at −1 V versus RHE. [103] The active sites consist of Cu(I) center in a distorted trigonal bipyramidal geometry, which allows the adsorption of CO 2 with η1-COO-like configuration to commence the catalysis, with a turnover frequency of ≈45 s −1 at −1 V versus RHE.…”
Section: Other Metal-based Catalystsmentioning
confidence: 99%
“…The active sites of AD‐Sn/N‐C were believed to be Sn–N x , which was similar to other M–N x structure. In addition to the well‐developed M–N x moiety, the transition metal atoms coordinated with N, S, and Cl atoms are stimulated to serve as the active sites of carbon‐rich NPMSACs, such as M–N x S y moiety or M–N x Cl y moiety. For instance, the S and N atoms were introduced on the electrochemically exfoliated graphene by high‐temperature pyrolysis treatment of dicyandiamide‐ and thiophene‐based precursors, where the two precursors were assembled with transition metal salt at a molecular scale via hydrothermal reaction and further converted to N/S‐codoped Ni‐based SAC …”
Section: Carbon‐rich Npmsacs For Crr and Hermentioning
confidence: 99%
“…106,107 Because their molecular structures can be accurately tailored, high selectivity for the desirable products can be achieved on molecular catalysts for electrochemical CO 2 RR. 94,96,108,109 Recently, Wang et al 94 reported that a 1,10-phenanthroline-Cu complex on a mesostructured rGO matrix can be active and selective for CO 2 RR over HER in an aqueous solution. The phen-Cu complex, made of 1,10-phenanthroline ligands and Cu 2+ ions, was synthesized from an assembly of CuCl 2 and phen in a solvent mixture of CH3OH/CH2Cl2 and immobilized on the rGO substrate.…”
Section: Molecular Catalysts/rgo-based Electrocatalystsmentioning
confidence: 99%